An Evaluation of the Effects of Shade on Open Space Thermal Comfort, and Establishing Thermal Comfort Zone - Shahrzad Talebsafa; Masoud Taheri Shahraeini; Xiaoshan Yang; Mohammadreza Rabiei (صفه)
The rapid growth of urbanisation in contemporary era has increased the human need for open space. One of the most important principles of open space design is to pay attention to thermal comfort in order to improve the quality of space and satisfy users. Numerous factors affect the thermal comfort quality of open spaces including shading; one of the most important ones. This study investigates the effect of shade on students' thermal comfort at Shahrood University of Technology in Iran during the hot season. For this purpose, field studies were conducted including the measurement of major climatic parameters, as well as the evaluation of the thermal perception of students by using thermal comfort questionnaires at four types of location in campus (under plants shade, building shade, horizontal shading (canopy), and sunlight) simultaneously. The Physiologically Equivalent Temperature (PET) is used here as a thermal comfort index. The neutral PET value of 21.9 °C and the maximum value in the PET comfort range of 26.9 °C are obtained for this study. The results show that there is a significant relationship between the location and the thermal comfort. The plants shade creates an acceptable thermal environment with more than 80% user satisfaction. After that, the canopy and the building shade also provide environmental satisfaction for the majority of people, while the most uncomfortable condition is in the sunlight position. Shaded locations decrease the PET value and thermal stress on sunny days and increase comfort levels as well as comfort hours during the day. Therefore, it can be concluded that creating shade and blocking direct solar radiation using vegetation or building elements can significantly improve outdoor thermal comfort during the hot season.